Serum IgM , IgG, TBIL, prothrombin activity (PTA) combined transient elastography in the diagnosis of cirrhosis with esophageal and gastric varices: serum markers, transient elastography in cirrhosis - Chaozhi Wang, Chaozhi Wang (Journal of Medical Biochemistry, 2025)
Objective: To explore the application and clinical value of Serum IgM , IgG, TBIL, prothrombin activity (PTA) combined transient elastography (TE) in diagnosing and assessing the degree of liver cirrhosis combined with esophageal and gastric varices (EGV). Methods: We chose 136 patients with cirrhosis and EGV admitted to the Liver Disease Department of our hospital from December 2022 to December 2024. The patients were divided into mild EGV (n=71), moderate EGV (n=40), and severe EGV (n=25) based on the gastroscopic results, and another 50 cases of healthy physical examination at the same period were admitted into the control group. All cases underwent liver TE, biochemical parameters, and immune parameters examination to observe the diagnostic efficacy of liver TE in cirrhosis combined with EGV and the degree of varices. Results: The differences in TBIL, ALT, AST, PTA, and other biochemical parameters between all of groups were not statistically significant (P > 0.05). The differences were not statistically significant for the four groups of IgM, IgG, and other immune indices (P > 0.05). There was no significant difference in blood flow among these groups (P > 0.05). The interior diameter (ID) of the portal vein, blood flow velocity, and liver stiffness values were significant (P < 0.05). Portal vein ID, blood velocity, and liver stiffness values showed well diagnostic efficacy in cirrhosis with EGV, and liver stiffness values were the best in evaluating cirrhosis with EGV (P < 0.05). Liver stiffness values were more effective in assessing the degree of varices in cirrhosis combined with EGV and the best in diagnosing cirrhosis combined with severe EGV (P < 0.05). Conclusion: The application of liver TE has a high value in diagnosing cirrhosis combined with EGV and their degree of varices, especially in identifying severe curves, which has good clinical value.